2017
DOI: 10.1108/ajim-09-2016-0155
|View full text |Cite
|
Sign up to set email alerts
|

Effective use of human physiological metrics to evaluate website usability

Abstract: Purpose The evaluation of website usability is the precondition and a critical step for website design and optimization. The purpose of this paper is to investigate and provide empirical evidence of the interrelationships between human physiological metrics and website usability. This study examines how eye-movement metrics and heart rate variability (HRV) evaluate website usability, and then affect users’ online surfing behavior. Design/methodology/approach A physiological measurement experiment is designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…During data discovery, researchers devote efforts to evaluating and understanding data by screening metadata (Pasquetto et al, 2019). Fixation duration can measure the depth of information processing (Qu et al, 2017). This paper measured participants' total fixation duration of metadata as one of the indicators of search effort.…”
Section: Methodsmentioning
confidence: 99%
“…During data discovery, researchers devote efforts to evaluating and understanding data by screening metadata (Pasquetto et al, 2019). Fixation duration can measure the depth of information processing (Qu et al, 2017). This paper measured participants' total fixation duration of metadata as one of the indicators of search effort.…”
Section: Methodsmentioning
confidence: 99%
“…The objective of these studies is to measure visual attention (fixation duration and fixation count) in the presence of marketing stimuli, such as online video or text reviews (Brand & Reith, 2022), Instagram posts (Badenes-Rocha et al, 2022), advertising (Felix & Borges, 2014, Grigaliunaite & Pipeleine, 2016;Ahmadopour et al, 2019), and wine labels (Monteiro et al, 2020). In the case of one study, eye-tracking was combined with a biometric technology used to measure heart rate variability for evaluating web usability (Qu et al, 2017). Electroencephalography (EEG) seems to be also a frequently chosen technique, especially for studies in Group 3.…”
Section: Table 2 Data Collection Instruments and Sample Sizementioning
confidence: 99%
“…Put differently, satisfaction may be considered as a perception of usability, and research has unequivocally demonstrated that such perceptions are important determinants of usage intention (e.g. Qu et al , 2017). Questionnaires are the typical means of collecting usability perception data, and over the years, a range of scales have been developed to measure this important concept.…”
Section: Related Workmentioning
confidence: 99%